Pituitary metastasis of hepatocellular carcinoma as the initial presentations: a case report and review of the literature - He, Qiang; Deng, Feng; Cai, Bowen; You, Chao; Zheng, Songping (Frontiers in Oncology, 2023)
Abstract Background: Extrahepatic metastasis of hepatocellular carcinoma (HCC) is common. However, pituitary metastasis of HCC is extremely rare. Our case may be helpful extend the understanding of the disease. Case presentation: A 65-year-old male presented to the outpatient department for unexplained headache and ptosis for one month. Brain imaging showed a slight enhancement tumor in the pituitary fossa, and the endocrinological assessment was normal. We considered the tumor as a non-functioning pituitary adenoma before surgery. Then, the tumor was ressected by endonasal endoscopic transsphenoidal approach. The histopathological examination results confirmedrevealed the pituitary metastasis of HCC. Additional abdominal imaging revealed tumors were located in the left and right liver lobes with portal vein invasion and bilateral ilium metastases. After a multi-disciplinary cooperation, the patient chosed choose chemotherapy. Conclusions: We report a case of HCC metastasis to the pituitary gland that initially presented with neurological symptoms. We should consider the possibility of pituitary metastasis in HCC patients. Keywords: Hepatocellular carcinoma, Pituitary metastasizes, Case report